Method for preparing electroactive materials for metal ion batteries
By using CVI technology to deposit electroactive materials on the porous carbon framework and adjusting the particle size through the crushing step, the mechanical stress and electrochemical capacity loss caused by volume changes in the charge and discharge cycle of silicon anode materials in lithium-ion batteries are solved, and efficient and uniform electrochemical performance is achieved.
Patent Information
- Application Number
- CN201980092696.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-02-13
- Filing Date
- 2019-12-20
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2039-12-20
AI Technical Summary
In existing lithium-ion batteries, graphite is a theoretical capacity limitation as an anode active material, and silicon is a potential alternative material that causes mechanical stress and electrochemical capacity loss due to volume changes during the charge and discharge cycle.
Electroactive materials such as silicon are deposited into micropores and mesopores of porous carbon frameworks in a fluidized bed reactor by chemical vapor permeation (CVI) technology to form composite particles and adjust the particle size through the pulverization step to suit commercial scale production.
It realizes uniform deposition and efficient dispersion of electroactive materials, reduces mechanical stress caused by volume changes, improves the retention rate of electrochemical capacity, and is suitable for large-scale commercial production.
Smart Images

Figure BDA0003221752150000281 
Figure BDA0003221752150000291
Abstract
Description
[0001] The present invention relates generally to electroactive materials suitable for use in electrodes of rechargeable metal ion batteries, and more particularly to methods for preparing particulate materials having high electrochemical capacity suitable for use as anode active materials in rechargeable metal ion batteries.
[0002] Rechargeable metal ion batteries are widely used in portable electronic devices, such as mobile phones and laptops, and are increasingly used in electric vehicles or hybrid vehicles. Rechargeable metal ion batteries generally include an anode layer, a cathode layer, an electrolyte for transporting metal ions between the anode layer and the cathode layer, and an electrically insulating porous separator disposed between the anode and the cathode. The cathode generally includes a metal current collector having a metal oxide composite material layer containing metal particles, and the anode generally includes a metal current collector having an electroactive material layer, and the electroactive material is defined herein as a material that can embed and release metal ions during the charging and discharging of the battery. For the avoidance of doubt, the terms "cathode" and "anode" are used herein in the following sense: the battery is connected to both ends of the load so that the cathode is the positive electrode and the anode is the negative electrode. When the metal ion battery is charged, the metal ions are transported from the cathode layer containing the metal ions to the anode via the electrolyte and are embedded in the anode material. The term "battery" herein refers to both a device containing a single anode and a single cathode and a device containing multiple anodes and / or multiple cathodes.
[0003] There is interest in improving the gravimetric and / or volumetric capacity of rechargeable metal ion batteries. The use of lithium ion batteries has provided substantial improvements when compared to other battery technologies, but there is still room for further development. To date, commercial lithium ion batteries have been largely limited by the use of graphite as the anode active material. When the graphite anode is charged, lithium is intercalated between the graphite layers to form a lithium ion battery with the empirical formula Li x C6 (where x is greater than 0 and less than or equal to 1). Thus, the maximum theoretical capacity of graphite in lithium-ion batteries is 372 mAh / g, with actual capacities slightly lower (approximately 340 to 360 mAh / g). Other materials such as silicon, tin, and germanium can intercalate lithium at significantly higher capacities than graphite, but have not been widely used commercially due to difficulties in maintaining sufficient capacity over multiple charge / discharge cycles.
[0004] In particular, silicon is considered a promising graphite substitute for making rechargeable metal ion batteries with high weight and volumetric capacity due to its very high lithium capacity (see, for example, Insertion Electrode Materials for rechargeable Lithium Batteries, Winter, M et al., Adv. Mater. 1998, 10, No. 10). At room temperature, the theoretical maximum specific capacity of silicon in lithium ion batteries is about 3,600 mAh / g (based on Li 15 However, the use of silicon as an anode material is complicated by the large volume change during charge and discharge.
[0005] The insertion of lithium into bulk silicon results in a substantial increase in the volume of the silicon material, which increases to 400% of its original volume when silicon is lithiated to its maximum capacity, and repeated charge-discharge cycles induce significant mechanical stress in the silicon material, leading to fracture and delamination of the silicon anode material. The volume shrinkage of silicon particles during delithiation may result in loss of electrical contact between the anode material and the current collector. Another difficulty is that the solid electrolyte interface (SEI) layer formed on the silicon surface does not have sufficient mechanical tolerance to accommodate the expansion and contraction of silicon. As a result, the newly exposed silicon surface leads to further electrolyte decomposition and increased SEI layer thickness as well as irreversible lithium consumption. These damage mechanisms together lead to unacceptable electrochemical capacity loss during continuous charge and discharge cycles.
[0006] A variety of approaches have been proposed to overcome the problems associated with the volume changes observed when silicon-containing anodes are charged. The most common approach to addressing the irreversible capacity loss of silicon-containing anodes is to use some form of finely structured silicon as the electroactive material. Fine silicon structures such as silicon films and silicon nanoparticles with cross-sections below about 150 nm have been reported to be more tolerant of volume changes during charge and discharge than silicon particles in the micrometer size range. However, none of them is particularly suitable for commercial-scale applications in their unmodified form; nanosized particles are difficult to prepare and handle, and silicon films do not provide sufficient bulk capacity. For example, nanosized particles tend to form agglomerates, making it difficult to obtain a usable dispersion of particles within the anode material matrix. In addition, the formation of agglomerates of nanosized particles leads to unacceptable capacity losses upon repeated charge-discharge cycles.
[0007] It is also generally known that electroactive materials such as silicon can be deposited in the pores of porous support materials such as activated carbon materials. These composite materials provide some of the beneficial charge-discharge properties of nanosized silicon particles while avoiding the handling difficulties of nanoparticles. For example, Guo et al. (Journal of Materials Chemistry A, 2013, pp. 14075-14079) disclose a silicon-carbon composite material in which a porous carbon substrate provides a conductive skeleton and silicon nanoparticles are deposited in a uniformly distributed pore structure of the substrate. SEI formation during the initial charge cycle is limited by the remaining pore volume so that the remaining silicon is not exposed to the electrolyte in subsequent charge cycles. It is known that the composite material has an improved capacity retention rate over multiple charge cycles, but the initial capacity of the composite material (in mAh / g) is significantly lower than the initial capacity of the silicon nanoparticles.
[0008] JP2003100284 discloses an active material comprising a carbon-based scaffold with small pores branching from some larger pores. The electroactive material (eg silicon) is randomly located on the walls of both the large and small pores, as well as on the outer surface of the carbon-based scaffold.
[0009] It has been observed that the performance of composite materials comprising a porous carbon framework and an electroactive material such as silicon located within the porous carbon framework can be optimized by using a porous carbon framework with a specific pore structure and a controlled ratio of electroactive material to available pore volume. 50 ) are beneficial for the desired end use of these composite materials in metal ion batteries. However, it is difficult to prepare these composite materials in an efficient and consistent manner, especially on a large scale for commercial use. It is difficult to control the deposition of the electroactive material so that it is deposited in the desired location within the pores of the porous carbon framework. It is also difficult to control the deposition when preparing a product with a desired low particle size. The present invention is intended to address this problem.
[0010] Chemical vapor infiltration (CVI) is a process of using a reactive gaseous precursor to infiltrate a porous substrate material with another phase. The porous substrate is placed on a perforated metal plate, and a mixture of a carrier gas and a gaseous precursor is passed through the porous substrate maintained at a high temperature. The gaseous precursor reacts chemically within the porous structure of the substrate material at a high temperature and is deposited on the inner surface of the pore space. The CVI process improves the density of the porous substrate material. CVI is particularly useful because it has very little damage to the geometry of the porous substrate. In addition, a high degree of uniformity in the substrate can be achieved by controlling the purity of the reactive gaseous precursor and the pressure and temperature of the infiltration.
[0011] It has been determined that chemical vapor infiltration (CVI) can be used to deposit electroactive materials into microporous and / or mesoporous carbon materials having a particle size of less than 20 μm to obtain composite materials with desirable electrochemical properties. In the present invention, CVI refers in particular to a process in which a gaseous precursor of an electroactive material, such as silicon, is thermally decomposed on a surface to deposit the electroactive material in elemental form at the surface and to form gaseous byproducts, which allow deposition onto internal surfaces, in particular the surfaces of the pore walls.
[0012] Typically, the low diffusivity of the gaseous silicon precursors used in CVI of silicon compounds to micropores and / or mesoporous systems or other gaseous precursors for other electroactive materials means that a kinetic-limited (surface reaction-limited) deposition scheme must be used. However, from a processing perspective, this adds a lot of complexity. A major problem is that in large-volume samples and reactor systems for high-throughput / large-batch and continuous processing, it is difficult to ensure the high thermal uniformity and mass transfer uniformity required to maintain a uniform deposition rate relative to the reactor position, process time, and particle pore system position. Therefore, it is difficult to use CVI on a commercially available scale to deposit electroactive materials into the pores of porous carbon frameworks. It is believed that there is no universal commercial manufacturing approach to use CVI as a deposition technique to specifically process powders in a size range of less than 20 μm.
[0013] Fluidized bed reactor (FBR) can be used to carry out CVI.FBR has various applications in industry.They provide the means of very efficient gas-solid contact, and provide uniform temperature distribution in bed simultaneously.This is mainly realized by fluidizing the particles using airflow and by contacting all surfaces with reactant gas.FBR satisfies multiple in the above-mentioned mass transfer and heat transfer problems.When realizing fluidization, particularly when compared with alternative powder treatment schemes for carrying out CVI such as fixed bed and rotary furnace, excellent solid-solid and gas-solid mixing is observed.
[0014] The fluidization behavior of particles is divided into one group according to the size and density of the particles. These groups are referred to as Geldart group A, B, C and D materials. Group A, B and D materials can be fluidized with / without bubbles and slugging behavior. However, Geldart C includes low-size, low-density materials, and they may be difficult to fluidize due to the cohesive forces that exist as a result of the small size. Low-particle size carbon powders can be considered as Geldart group C materials.
[0015] As described in Vahlas et al., Principles and applications of CVD powder technology, Materials Science and Engineering R 53 (2006) 1-72, the use of FBR-chemical vapor deposition (CVD) (including CVI) has been used to deposit a variety of catalytic metals and non-metals on porous and non-porous materials.
[0016] However, carbon powders less than 20 μm in size tend to form agglomerates when used in FBR due to the strength of the inter-particle cohesive forces at this length scale. This is a problem because fluidization may only occur as large millimeter-sized agglomerates, rather than fluidization of individual particles, which leads to related problems related to mass transfer rates within agglomerates. In addition, there may be no fluidization of the carbon powder, but instead channeling ("rat-holing") caused by the locally applied shear forces applied by the gas flow being insufficient to break the cohesive forces between the particles (i.e., the gas finds a way around the powder bed, rather than passing through it). For these reasons, FBR has been considered unsuitable for processes involving carbon powders less than 20 μm in size. SUMMARY OF THE INVENTION
[0018] The present invention uses chemical vapor infiltration into porous carbon powders in a fluidized state, enabling control of the kinetic and thermodynamic conditions of the infiltration reaction and ensuring that each porous carbon particle experiences a similar chemical and thermal environment. In essence, the present invention treats individual micron-sized powders as micro-infiltration substrates, reducing the characteristic length scales of precursor diffusion and reaction and facilitating the transition to a continuous process for batch production.
[0019] In a first aspect, the present invention provides a method for preparing a particulate material comprising a plurality of composite particles, the method comprising:
[0020] (a) providing a particulate porous carbon framework comprising micropores and / or mesopores, wherein the porous carbon framework has a D 50 The particle size is at least 20 μm;
[0021] (b) depositing an electroactive material selected from silicon, tin, aluminum, germanium and alloys thereof into the micropores and / or mesopores of the porous carbon framework using chemical vapor infiltration in a fluidized bed reactor to provide intermediate particles; and
[0022] (c) pulverizing the intermediate particles to provide the composite particles.
[0023] Thus, the method of the present invention utilizes the advantages of CVI to deposit the electroactive material into the pores of the porous carbon framework, thereby providing a functional nanostructure containing the electroactive material. The method also utilizes the advantages of using FBR for CVI. The method also avoids the difficulties of using FBR with low particle size carbon powders because the method uses D 50 A particulate porous carbon skeleton with a particle size of at least 20 μm is used as a raw material. The pulverizing step means that the method can be used to provide composite particles with a reduced particle size compared to the raw material, which is considered to be useful for the desired end use in metal ion batteries. In particular, composite particles within these size ranges are ideally suitable for composite membrane negative electrodes (or "anodes") of metal ion batteries due to their dispersibility in slurries, their structural robustness, and their capacity retention with repeated charge-discharge cycles. The thickness of such composite films is generally less than 100 μm, or less than 50 μm, and smaller particle sizes also help to achieve a denser film with uniform thickness. Therefore, the method of the present invention provides an effective method for preparing composite particles suitable for large-scale commercial use.
[0024] It may seem counterintuitive to use CVI to prepare intermediate composite particles in a FBR and then pulverize the intermediate particles. In particular, the pulverization step may be considered to damage the functional nanostructure of the intermediate particles obtained by the CVI process, i.e., the electroactive material deposited in the pores of the carbon skeleton. However, the inventors have found that pulverization can be performed without a significant level of damage due to the relative μm-length scale of the rupture compared to the nm-length scale of the functional units of the composite particles. Because the carbon skeleton includes micropores and / or mesopores, the desired properties are retained in the product upon pulverization.
[0025] The method of the present invention enables the properties of the porous carbon framework material to be selected to provide a final product having a set of desired properties. For example, because the pulverization step can be performed without significant damage to the pore structure, the porous carbon framework with a specific pore structure is selected to enable the preparation of a product with a specific microporous and / or mesoporous structure.
[0026] The electroactive material may be silicon or tin. Preferably, the electroactive material is silicon. The electroactive material may optionally contain a small amount of one or more dopants. Suitable dopants include boron and phosphorus, other n-type or p-type dopants or nitrogen. When silicon is the electroactive material, the silicon may also be doped with a small amount of one or more other electroactive materials such as tin, aluminum and germanium. Preferably, the dopant is present in a total amount of no more than 2% by weight based on the total amount of the electroactive material and the one or more dopants.
[0027] For the avoidance of doubt, the term "particle size" as used herein refers to the equivalent spherical diameter (esd), i.e., the diameter of a sphere having the same volume as a given particle, wherein the particle volume is understood to include the volume of any intra-particle pores. 50 ” and “D 50 "Particle size" refers to the median particle size based on volume, that is, the diameter at which 50% of the volume of the particle population is below a certain diameter. As used herein, the term "D 10 ” and “D 10 The term "particle size" as used herein refers to the 10th percentile volume-based median particle size, i.e., the diameter below which 10% of the volume of the particle population is measured. 90 ” and “D 90 "Particle size" refers to the 90th percentile volume-based median particle size, i.e., the diameter below which 90% of the volume of the particle population is measured.
[0028] The term "D" used herein to define particle size distribution should be n ” is used in this document to define the pore size distribution term “PD n " As used herein, the general term "PD n "Pore diameter" refers to the nth percentile pore diameter based on volume, based on the total volume of micropores and mesopores. For example, as used herein, the term "D 50 The term "pore size" refers to the pore size at which 50% of the total micropore and mesopore volume (represented by P1) is lower than a certain pore size.
[0029] For the avoidance of doubt, in order to determine the PD n value, without taking into account any macropore volume (pores larger than 50 nm).
[0030] Particle size and particle size distribution can be determined by conventional laser diffraction techniques according to ISO 13320:2009. Laser diffraction relies on the principle that particles will scatter light at angles that vary depending on the size of the particle, and that a plurality of particles will produce a scattered light pattern defined by intensity and angle that can be related to the particle size distribution. A variety of laser diffraction instruments are commercially available for rapid and reliable determination of particle size distribution. Unless otherwise stated, particle size distribution measurements indicated or reported herein are made by conventional Malvern Mastersizer from Malvern Instruments. TM Measured by Malvern Mastersizer 3000 particle size analyzer. TMThe 3000 particle size analyzer operates by projecting a helium-neon gas laser beam through a transparent pool containing particles of interest suspended in an aqueous solution. The light that hits the particles is scattered by angles inversely proportional to the particle size, and a photodetector array measures the intensity of the light at multiple predetermined angles, and the particle size distribution is determined by computer processing the intensity measured at different angles using standard theoretical principles. The laser diffraction values reported herein are obtained using wet dispersions of particles in distilled water. The particle refractive index is 3.50, and the dispersant index is 1.330. The particle size distribution is calculated using the Mie scattering model.
[0031] Porous carbon skeleton
[0032] Porous carbon framework 50 The particle size is at least 20 μm. In this way, the porous carbon framework can be easily used in FBR. Optionally, the D 50 The particle size is in the range of 20 to 1000 μm, 30 to 500 μm or 60 to 150 μm. Optionally, the D of the porous carbon framework is 50 The particle size is at least 30 μm, at least 40 μm, or at least 50 μm, or at least 60 μm, or at least 70 μm, or at least 80 μm. Optionally, the D of the porous carbon framework is 50 The particle size is not more than 1000 μm, or not more than 500 μm, or not more than 250 μm, or not more than 150 μm.
[0033] Optionally, the D of the porous carbon framework 10 The particle size is at least 5 μm, at least 15 μm, at least 40 μm, or at least 50 μm, or at least 60 μm, or at least 70 μm. By maintaining D 10 Particle sizes above these values advantageously avoid the presence of large amounts of carbon skeletons having small particle sizes that may be unsuitable for FBR.
[0034] Optionally, the D of the porous carbon framework 90 The particle size is no more than 1,500 μm, or no more than 1,000 μm, or no more than 750 μm, or no more than 500 μm, or no more than 200 μm. Optionally, the D of the porous carbon framework 98 The particle size is not more than 1,550 μm, or not more than 1,050 μm, or not more than 800 μm, or not more than 550 μm, or not more than 250 μm. 90 and / or D 98 Particle sizes below these values advantageously avoid the presence of large amounts of carbon frameworks having large particle sizes that may be unsuitable for CVI.
[0035] For example, the porous carbon framework may have a D of at least 15 μm. 10Particle size, at least 20 μm D 50 Particle size and D not exceeding 200 μm 90 The porous carbon framework may have a particle size of at least 5 μm. 10 Particle size, D in the range of 20 to 250 μm 50 Particle size, not exceeding 750μm D 90 Particle size and D not exceeding 1,000 μm 98 The porous carbon framework may have a particle size of at least 5 μm. 10 Particle size, D in the range of 20 to 200 μm 50 Particle size, not exceeding 500μm D 90 Particle size and D not exceeding 800μm 98 The porous carbon framework may have a particle size of at least 40 μm. 10 Particle size, D in the range of 60 to 150 μm 50 Particle size, and D not exceeding 200 μm 90 Particle size and D not exceeding 250 μm 98 Particle size.
[0036] The porous carbon framework preferably has a narrow size distribution span. For example, the particle size distribution span (defined as (D 90 -D 10 ) / D 50 ) is preferably 5 or less, more preferably 4 or less, more preferably 3 or less, more preferably 2 or less, and most preferably 1.5 or less. By maintaining a narrow size distribution span, consistent deposition of the electroactive material into the pores of the carbon framework can be more easily achieved.
[0037] The porous carbon framework suitably comprises a three-dimensional interconnected open pore network comprising a combination of micropores and / or mesopores and optionally a small volume of macropores. According to IUPAC terminology, the term "micropore" is used herein to refer to pores with a diameter less than 2 nm, the term "mesopore" is used herein to refer to pores with a diameter of 2 to 50 nm, and the term "macroporous" is used to refer to pores with a diameter greater than 50 nm.
[0038] References herein to the volumes of micropores, mesopores, and macropores in a porous carbon framework, as well as any reference to the distribution of pore volume within the porous carbon framework, refer to the internal pore volume of the porous carbon framework alone (i.e., in the absence of any electroactive material or other material occupying some or all of the pore volume).
[0039] The volume fraction of micropores (based on the total volume of micropores and mesopores) is represented in this paper by the symbol , and the volume fraction of mesopores (based on the total volume of micropores and mesopores) is represented by the symbol So it will be understood
[0040] The porous carbon framework is characterized by the pore volume in the form of micropores and / or mesopores. The total volume of micropores and mesopores (i.e., the total pore volume in the range of 0 to 50 nm) may be referred to herein as P1cm 3 / g, where P1 represents a dimensionless natural number. The value of P1 is also used to relate the available pore volume in the porous carbon framework to the weight ratio of the electroactive material to the porous carbon framework in the final product.
[0041] For the avoidance of doubt, P1 as used herein relates to the pore volume of the porous carbon skeleton when measured alone, i.e., the pore volume of the porous carbon skeleton in the absence of silicon or any other material occupying the pores of the porous carbon skeleton. Similarly, the volume of micropores, mesopores and macropores in the porous carbon skeleton mentioned herein and any distribution of pore volume within the porous carbon skeleton refer to the internal pore volume of the porous carbon skeleton alone (i.e., in the absence of any silicon or other material occupying the pore volume).
[0042] The value of P1 may be in the range of 0.4 to 2.5. Thus, the pore volume of the porous carbon framework may be at least 0.4 cm 3 / g and at most 2.5cm 3 / g.
[0043] The value of P1 may be in the range of 0.4 to 0.6. This corresponds to a low pore volume in the form of micropores and / or mesopores.
[0044] Alternatively, the value of P1 can be at least 0.6, or at least 0.65, or at least 0.7, or at least 0.75, or at least 0.8, or at least 0.85, or at least 0.9, or at least 0.95, or at least 1, or at least 1.05, or at least 1.1, or at least 1.2. The use of a high porosity carbon framework is advantageous because it enables a larger amount of silicon to be accommodated within the pore structure, and it has been found that a high porosity carbon framework in which the pore volume is primarily in the form of micropores and smaller mesopores has sufficient strength to accommodate the volume expansion of the electroactive material without fracturing or otherwise degrading the porous carbon framework.
[0045] The value of P1 may be no more than 2.5, or no more than 2.2, or no more than 2, or no more than 1.8, or no more than 1.6, or no more than 1.5, or no more than 1.4, or no more than 1.3, or no more than 1.2. The internal pore volume of the porous carbon framework is suitably limited to a value at which the increased fragility of the porous carbon framework outweighs the advantages of increased pore volume for accommodating larger amounts of electroactive material.
[0046] The value of P1 may be in the range of 0.4 to 2.5, or in the range of 0.6 to 2.5, or in the range of 0.7 to 2, or in the range of 0.7 to 1.2.
[0047] Volume fraction of micropores It may be at least 0.1, or in the range of 0.1 to 0.9. Preferably, Greater than 0.5, more preferably greater than 0.6, more preferably greater than 0.7, more preferably greater than 0.8.
[0048] A small portion of pores with diameters in the larger mesoporous range can advantageously facilitate access of the electrolyte to the electroactive material in the final product. Thus, pores with diameters in the range of 10 to 50 nm (i.e., larger mesopores) can optionally account for at least 1%, at least 2%, at least 5%, or at least 10% of the total micropore and mesopore volume of the porous carbon framework.
[0049] The pore size distribution of the porous carbon framework can be unimodal, bimodal or multimodal. As used herein, the term "pore size distribution" refers to the distribution of the pore size of the porous carbon framework relative to the cumulative total internal pore volume. Bimodal or multimodal pore size distributions may be preferred because the close proximity between the smallest pores and pores with larger diameters provides the advantage of efficient ion transport from the porous network to the electroactive material. Therefore, the composite particles prepared from the porous carbon framework have high ion diffusivity and thus improved rate performance.
[0050] Suitably, the bimodal or multimodal pore size distribution includes a peak pore size in the micropore range and a peak pore size in the mesopore size range, which differ from each other by 5 to 20 times, more preferably by about 10 times. For example, the porous carbon skeleton can have a bimodal pore size distribution, the bimodal pore size distribution including a peak at a pore size of 1.5nm and a peak at a pore size of 15nm. The porous carbon skeleton can have a bimodal pore size distribution, the bimodal pore size distribution including a peak at a pore size of 2nm and a peak at a pore size of 20nm. The porous carbon skeleton can have a bimodal pore size distribution, the bimodal pore size distribution including a peak at a pore size of 1.2nm and a peak at a pore size of 12nm.
[0051] According to the standard method described in ISO 15901-2 and ISO 15901-3, nitrogen adsorption was performed at 77 K down to 10 -6The relative pressure p / p0 of quenched solid density functional theory (QSDFT) is used to determine the total volume of micropores and mesopores and the pore size distribution of micropores and mesopores. Nitrogen adsorption is a technique for characterizing the porosity and pore size distribution of a material by condensing a gas in the pores of a solid. As the pressure increases, the gas first condenses in the pores with the smallest diameter, and the pressure increases until a saturation point is reached, at which all pores are filled with liquid. The nitrogen pressure is then gradually reduced to evaporate the liquid from the system. Analysis of the adsorption and desorption isotherms and the hysteresis between them enables the determination of pore volume and pore size distribution. Suitable instruments for measuring pore volume and pore size distribution by nitrogen adsorption include TriStar II and TriStar II Plus porosity analyzers (which can be obtained from Micromeritics Instrument Corporation in the United States), and Autosorb IQ porosity analyzer (which can be obtained from Quantachrome Instruments).
[0052] Nitrogen adsorption is effective for measuring the pore volume and pore size distribution of pores with a diameter of up to 50 nm, but is less reliable for pores with much larger diameters. For the purposes of the present invention, therefore, only pores with a diameter of up to 50 nm (including 50 nm) are used to determine the pore volume and pore size distribution. As described above, the value of P1 is determined by considering only pores with a diameter of up to 50 nm (including 50 nm) (i.e., only micropores and mesopores), and PDn and PDn are also determined relative to the total volume of only micropores and mesopores. and (discussed below).
[0053] Given the limitations of available analytical techniques, it is not possible to measure the pore volume and pore size distribution over the entire range of micropores, mesopores, and macropores using a single technique. In the case of porous carbon frameworks that include macropores, the volume of pores in the range of greater than 50 nm to a maximum of 100 nm is considered herein to have a P2 cm 3 The value of P2 is related to the pore volume of the porous carbon framework when measured alone, ie, in the absence of an electroactive material or any other material occupying the pores of the porous carbon framework.
[0054] For the avoidance of doubt, the value of P2 takes into account only pores with diameters from greater than 50 nm up to and including 100 nm, i.e. it includes only the volume of macropores with a diameter of up to 100 nm. For the determination of the value of P2, any pore volume of pore sizes below 50 nm measured by mercury intrusion is not taken into account. For the purposes of the present invention, the pore volume measured by mercury intrusion in the case of greater than 100 nm is assumed to be the interparticle porosity and is also not taken into account when determining the value of P2. As described above, nitrogen adsorption is used to characterize mesopores and micropores.
[0055] Mercury intrusion porosimetry is a technique for characterizing the porosity and pore size distribution of a material by applying varying levels of pressure to a sample of the material immersed in mercury. The pressure required to cause mercury to penetrate into the pores of the sample is inversely proportional to the size of the pores. The values obtained by mercury intrusion porosimetry reported herein are obtained according to ASTM UOP578-11, where for mercury at room temperature, the surface tension γ is 480 mN / m and the contact angle is is 140°. The density of mercury at room temperature is 13.5462 g / cm 3 A variety of high precision mercury porosimetry instruments are commercially available, such as the AutoPore IV series of automated mercury porosimeter, available from Micromeritics Instrument Corporation in the United States. For a complete overview of mercury porosimetry, reference may be made to PA Webb and C. Orr, "Analytical Methods in Fine Particle Technology", 1997, Micromeritics Instrument Corporation, ISBN 0-9656783-0.
[0056] The volume of macropores (and therefore the value of P2) is preferably small compared to the volume of micropores and mesopores (and therefore the value of P1). Although a small portion of macropores may be useful to facilitate the entry of electrolyte into the pore network, the advantages of the present invention are substantially obtained by accommodating silicon in micropores and smaller mesopores.
[0057] Therefore, according to the present invention, the total volume of the macropores in the porous carbon framework measured by mercury intrusion porosimetry is P2 cm 3 / g, wherein the value of P2 is preferably not more than 0.2×P1, or not more than 0.1×P1, or not more than 0.05×P1, or not more than 0.02×P1, or not more than 0.01×P1, or not more than 0.005×P1.
[0058] In preferred embodiments, the value of P2 is no more than 0.3, or no more than 0.25, or no more than 0.20, or no more than 0.15, or no more than 0.1, or no more than 0.05. As discussed above with respect to larger mesopores, a small pore volume fraction in the macropore range can advantageously promote access of the electrolyte to the electroactive material in the final product.
[0059] The open pore network optionally comprises a hierarchical pore structure, ie, a pore structure in which there is a degree of pore size ordering, with smaller pores branching from larger pores.
[0060] It should be understood that intrusion techniques such as gas adsorption and mercury intrusion are only valid for determining the pore volume of pores accessible to nitrogen or mercury from outside the porous carbon framework. The porosity values (P1 and P2) as specified herein should be understood to refer to the volume of open pores (pores accessible to the fluid from outside the porous carbon framework). In this article, when specifying porosity values, completely enclosed pores that cannot be identified by nitrogen adsorption or mercury intrusion should not be considered. Similarly, for determining the value of P1, any pore volume located in pores that are small enough to be below the detection limit of nitrogen adsorption is also not considered.
[0061] The porous carbon framework may comprise crystalline carbon or amorphous carbon, or a mixture of amorphous carbon and crystalline carbon.The porous carbon framework may be a hard carbon or a soft carbon framework, and may be suitably obtained by known procedures involving pyrolysis of polymers or organic matter.
[0062] As used herein, the term "hard carbon" refers to carbon atoms found predominantly as sp in nanoscale polyaromatic domains. 2 The polyaromatic domains are cross-linked using chemical bonds such as C-O-C bonds. Due to the chemical cross-linking between the polyaromatic domains, hard carbon cannot be converted into graphite at high temperatures. Hard carbon has graphite-like properties, which is reflected by the large G band (~1600 cm-1) in the Raman spectrum. -1 However, the carbon is not completely graphitic, as evidenced by the distinct D band (~1350 cm -1 ) is proved.
[0063] As used herein, the term "soft carbon" also refers to polyaromatic domains in which carbon atoms are found predominantly in sp 2 The polyaromatic domains in soft carbon are associated by intermolecular forces rather than crosslinked by chemical bonds, as in hard carbon. This means that they will graphitize at high temperatures. The porous carbon framework preferably contains at least 50% sp 2 Hybridized carbon (measured by XPS). For example, the porous carbon framework may suitably contain 50% to 98% sp 2Hybridized carbon, 55% to 95% sp 2 Hybridized carbon, 60% to 90% sp 2 Hybridized carbon, or 70% to 85% sp 2 Hybridized carbon.
[0064] A wide variety of different materials can be used to prepare suitable porous carbon skeletons. Examples of organic materials that can be used include: plant biomass, including lignocellulosic materials (such as coconut shells, rice husks, wood, etc.), and fossil carbon sources, such as coal. Examples of polymer materials that form porous carbon skeletons upon pyrolysis include: phenolic resins, novolac resins, asphalt, melamine, polyacrylates, polystyrene, polyvinyl alcohol (PVA), polyvinyl pyrrolidone (PVP), and various copolymers including monomer units of acrylates, styrene, α-olefins, vinyl pyrrolidone and other ethylenically unsaturated monomers. Depending on the raw materials and conditions of the pyrolysis process, a variety of different hard carbon materials are available in the art.
[0065] The porous carbon framework may be subjected to a chemical or gas activation process to increase the volume of the mesopores and micropores. Suitable activation processes include contacting the pyrolytic carbon with one or more of oxygen, water vapor, CO, CO2, and KOH at a temperature in the range of 600 to 1000°C.
[0066] Mesopores can also be obtained by known templating processes using removable pore formers such as MgO and other colloidal or polymer templates that can be removed by thermal or chemical means after pyrolysis or activation.
[0067] The BET surface area of the porous carbon framework is preferably at least 750 m 2 / g, or at least 1,000m 2 / g, or at least 1,250m 2 / g, or at least 1,500m 2 / g. The term "BET surface area" as used herein should be considered to mean the surface area per unit mass calculated from the measurement results of the physical adsorption of gas molecules on the solid surface using the Brunauer-Emmett-Teller principle according to ISO9277. Preferably, the BET surface area of the conductive porous particle skeleton does not exceed 4,000 m 2 / g, or not more than 3,500m 2 / g, or not more than 3,250m 2 / g, or not more than 3,000m 2 / g.
[0068] As discussed above, the inventors have recognized that because the carbon skeleton includes micropores and / or mesopores, the desired properties are retained in the product upon comminution. Therefore, the present invention can enable the desired properties of the composite particle product to be targeted by controlling the pore structure of the porous carbon skeleton. Some types of porous carbon skeletons are discussed below and can be used in the present invention to provide some types of composite particle products. It is to be understood that the characteristics of the porous carbon skeletons of the types discussed below should be considered to be combined with the characteristics of the porous carbon skeletons discussed above, such as particle size.
[0069] Porous carbon skeleton 1
[0070] The porous carbon framework 1 is characterized by a P1 value of at least 0.5 and a PD of no more than 5 nm. 50 Aperture.
[0071] Preferably, the value of P1 is at least 0.75, or at least 0.8, or at least 0.85, or at least 0.9, or at least 0.95, or at least 1, such as at least 1.05, or at least 1.1, or at least 1.15, or at least 1.2.
[0072] The value of P1 may be at most 2.5. Preferably, the value of P1 may be no more than 2.2, or no more than 2, or no more than 1.8, or no more than 1.6, or no more than 1.5, or no more than 1.4, or no more than 1.3, or no more than 1.2, or no more than 1.1, or no more than 1.0, or no more than 0.9. More preferably, P 1 The value of does not exceed 1.2, or does not exceed 1.1, or does not exceed 1.0, or does not exceed 0.9.
[0073] Preferably, the value of P1 can be, for example, in the range of 0.7 to 1.5, or in the range of 0.75 to 1.4, or in the range of 0.7 to 1.3, or in the range of 0.75 to 1.3, or in the range of 0.7 to 1.2, or in the range of 0.75 to 1.2, or in the range of 0.7 to 1, or in the range of 0.75 to 1, or in the range of 0.7 to 0.9, or in the range of 0.75 to 0.9.
[0074] PD of porous carbon framework 1 50 The pore size is preferably no more than 4 nm, or no more than 3 nm, or no more than 2.5 nm, or no more than 2 nm. Preferably, the PD of the porous carbon skeleton 50 The pore size is at least 0.8 nm, or at least 1 nm, or at least 1.2 nm. It is therefore particularly preferred that more than 50% of the total micropore and mesopore volume is in the form of micropores.
[0075] More preferably, at least 80% of the total micropore and mesopore volume of the porous carbon framework 1 is in the form of pores having a diameter not exceeding 5 nm. 80 The pore diameter is preferably no greater than 5 nm, or no greater than 4 nm, or no greater than 3 nm, or no greater than 2.5 nm, or no greater than 2 nm.
[0076] The volume of the larger mesopores in the porous carbon framework 1 is preferably limited so that the PD 90 The pore diameter is no more than 20nm, or no more than 15nm, or no more than 12nm, or no more than 10nm, or no more than 8nm, or no more than 6nm, or no more than 5nm, or no more than 4nm, or no more than 3nm, or no more than 2.5nm, or no more than 2nm.
[0077] Preferably, PD 95 The pore diameter is no more than 20 nm, or no more than 15 nm, or no more than 12 nm, or no more than 10 nm.
[0078] Porous carbon skeleton 2
[0079] The porous carbon framework 2 is characterized by a P1 value of at least 0.6 and a micropore volume fraction in the range of 0.1 to 0.9.
[0080] The porous carbon framework 2 is also characterized by a pore volume that is generally biased toward smaller pores, such that at least 75% of the total micropore and mesopore volume is in the form of pores having a diameter of no greater than 20 nm. The volume fraction of pores having a diameter of no greater than 20 nm (based on the total volume of micropores and mesopores) is represented herein by the symbol Indicates that the symbol and The corresponding volume fractions are used to define pores with diameters not exceeding 10 nm and not exceeding 5 nm, respectively.
[0081] Preferably, the value of P1 is at least 0.65, or at least 0.7, or at least 0.75, or at least 0.8, or at least 0.85, or at least 0.9, or at least 0.95, or at least 1. Optionally, P1 can be at least 1.05, or at least 1.1, or at least 1.15, or at least 1.2. The value of P1 can be up to 2.2. More preferably, the value of P1 does not exceed 2.2, or does not exceed 1.8, or does not exceed 1.6, or does not exceed 1.5, or does not exceed 1.4, or does not exceed 1.3, or does not exceed 1.2.
[0082] Preferably, the value of P1 can be, for example, in the range of 0.6 to 1.4, or in the range of 0.65 to 1.4, or in the range of 0.7 to 1.4, or in the range of 0.75 to 1.4, or in the range of 0.6 to 1.3, or in the range of 0.65 to 1.3, or in the range of 0.7 to 1.3, or in the range of 0.75 to 1.3, or in the range of 0.6 to 1.2, or in the range of 0.65 to 1.2, or in the range of 0.7 to 1.2, or in the range of 0.6 to 1, or in the range of 0.65 to 1, or in the range of 0.7 to 1, or in the range of 0.75 to 1, or in the range of 0.6 to 0.9, or in the range of 0.65 to 0.9, or in the range of 0.7 to 0.9, or in the range of 0.75 to 0.9.
[0083] The value of is preferably in the range of 0.15 to 0.85, more preferably in the range of 0.2 to 0.8. In some embodiments, Preferably, it is in the range of 0.45 to 0.85, or in the range of 0.5 to 0.8, or in the range of 0.6 to 0.8, thereby particularly utilizing the high capacity retention of very fine electroactive material nanostructures located in the micropores. In other cases, Preferably it is in the range from 0.2 to 0.5, or in the range from 0.3 to 0.5, in order to particularly exploit the opportunities of high electroactive material loadings.
[0084] Preferably, It is at least 0.8, more preferably at least 0.85, more preferably at least 0.9.
[0085] Preferably, based on the total volume of micropores and mesopores, is at least 0.75, or at least 0.8, or at least 0.85. Preferably, based on the total volume of micropores and mesopores, is at least 0.75, or at least 0.8, or at least 0.85. Thus, at least 75% of the total micropore and mesopore volume of the porous carbon framework is preferably in the form of pores having a diameter of no more than 10 nm and more preferably no more than 5 nm.
[0086] Porous carbon skeleton 3
[0087] The porous carbon framework 3 is characterized by a P1 value of at least 0.6 and a PD of no more than 2 nm. 50 Aperture.
[0088] Preferably, the value of P1 is at least 0.75, or at least 0.8, or at least 0.85. Optionally, P1 can be at least 0.9, or at least 0.95, or at least 1, or at least 1.05, or at least 1.1, or at least 1.15, or at least 1.2. Typically, the value of P1 may not exceed 2.5. More preferably, the value of P1 does not exceed 2.4, or does not exceed 2.2, or does not exceed 2, or does not exceed 1.8, or does not exceed 1.6, or does not exceed 1.5, or does not exceed 1.4, or does not exceed 1.3, or does not exceed 1.2, or does not exceed 1.1, or does not exceed 1.0, or does not exceed 0.9.
[0089] Preferably, the value of P1 can be, for example, in the range of 0.6 to 1.4, or in the range of 0.65 to 1.4, or in the range of 0.7 to 1.4, or in the range of 0.75 to 1.4, or in the range of 0.7 to 1.3, or in the range of 0.75 to 1.3, or in the range of 0.7 to 1.2, or in the range of 0.75 to 1.2, or in the range of 0.7 to 1, or in the range of 0.75 to 1, or in the range of 0.7 to 0.9, or in the range of 0.75 to 0.9.
[0090] PD of porous carbon framework 3 50 The pore diameter is preferably no greater than 1.8 nm, or no greater than 1.6 nm, or no greater than 1.4 nm, or no greater than 1.2 nm, or no greater than 1 nm.
[0091] Preferably, at least 80% of the total micropore and mesopore volume of the porous carbon framework 3 is in the form of pores having a diameter not exceeding 5 nm. 80 The pore size is preferably no more than 5 nm, or no more than 4.5 nm, or no more than 4 nm, or no more than 3.5 nm, or no more than 3 nm, or no more than 2.5 nm, or no more than 2.2 nm, or no more than 2 nm, or no more than 1.8 nm, or no more than 1.6 nm.
[0092] PD 90 The pore diameter is preferably no greater than 10 nm, no greater than 8 nm, or no greater than 6 nm, or no greater than 5 nm, or no greater than 4 nm, or no greater than 3 nm, or no greater than 2.5 nm, or no greater than 2 nm.
[0093] Preferably, PD 95 The pore diameter does not exceed 15 nm, or does not exceed 12 nm, or does not exceed 10 nm.
[0094] CVI / FBR
[0095] A laboratory-scale FBR can be used to contact the porous carbon framework with a gaseous precursor containing an electroactive material (e.g., silane) to deposit the electroactive material in the micropores and / or mesopores of the framework via CVI. Nitrogen can be used as an inert fluidizing gas, but other inert gases such as argon, hydrogen, or helium may also be used. It will be appreciated that in the method of the present invention, the porous carbon framework is fluidized in a FBR.
[0096] The method of the present invention uses CVI of a gaseous precursor of an electroactive material into the pore structure of a porous carbon framework. Preferably, the gaseous precursor is a silicon-containing gas.
[0097] Suitable silicon-containing precursors include silane (SiH4), disilane (Si2H6), trisilane (Si3H8), tetrasilane (Si4H 10 ), or a chlorosilane such as trichlorosilane (HSiCl3), or a methylchlorosilane such as methyltrichlorosilane (CH3SiCl3) or dimethyldichlorosilane ((CH3)2SiCl2). Preferably, the silicon-containing precursor is a silane.
[0098] The CVI process can also use a gaseous precursor of a dopant material to deposit the doped electroactive material into the micropores and / or mesopores of the porous carbon framework. When the dopant is boron, suitable precursors include borane (BH3), triisopropyl borate ([(CH3)2CHO]3B), triphenylborane ((C6H5)3B) and tris(pentafluorophenyl)borane (C6F5)3B, preferably borane. When the dopant is phosphorus, a suitable precursor is phosphine (PH3).
[0099] The precursor can be used in pure form, or more generally as a mixture diluted with an inert carrier gas such as nitrogen or argon. For example, the precursor can be used in an amount in the range of 0.5 to 20 volume %, or 1 to 10 volume %, or 1 to 5 volume % based on the total volume of the precursor and the inert carrier gas. The CVI process is suitably carried out at a low gaseous precursor partial pressure, and the total pressure is below atmospheric pressure (101.3 kPa) (e.g., 50 to 101.3 kPa), and the remaining partial pressure is supplemented to atmospheric pressure using an inert filler gas such as hydrogen, nitrogen or argon.
[0100] The temperature of the CVI process is selected to pyrolyze the precursor into an electroactive material. The CVI process is suitably carried out at a temperature in the range of 200 to 1,250°C, or in the range of 400 to 700°C, or in the range of 400 to 600°C, or in the range of 400 to 550°C, or in the range of 450 to 550°C, or in the range of 450 to 500°C. Preferably, the CVI process is carried out at a temperature in the range of 400 to 500°C, preferably 400 to 450°C or 450 to 500°C. The CVI process is preferably carried out above the minimum fluidization velocity (Umf) of the granular material. Preferably, the superficial velocity is higher than the minimum fluidization velocity (Umf) of the granular material. The minimum fluidization velocity (Umf) is generally a measured amount, and its value varies according to particle size, particle density and gas viscosity. The minimum fluidization velocity defines the flow rate of the gas that must be supplied to the reaction vessel to achieve the velocity of the particles when being lifted to a "fluid-like" state. The flow rates of the CVI process are suitably selected to provide good solid-solid and solid-gas mixing and minimal particle carryover from the reactor.The CVI process is suitably carried out in the range of 1 to 20 times the minimum fluidisation velocity (Umf).
[0101] Without wishing to be bound by theory, it is believed that when the porous carbon framework particle size is controlled in the manner discussed above, the penetration of the electroactive material is kinetically controlled. It is believed that the kinetic control of the penetration will result in composite particles in which the electroactive material is uniformly distributed. After a certain amount of electroactive material is deposited, this may result in the closure of pores over the entire volume of the framework. Controlling the particle size of the porous carbon framework has the following advantages: achieving high penetration efficiency over the temperature and concentration range used in the CVI process; while also making the framework suitable for fluidization in the traditional sense (such as Geldert A group).
[0102] Crushing
[0103] The method of the present invention comprises a step of comminuting the intermediate particles to provide the composite particles. The comminuting step causes the particle size of the composite particles to be lower than the particle size of the particulate porous carbon framework. One benefit of the present invention is that the comminuting step enables the use of CVI in a FBR as a process suitable for large-scale commercial use, while providing a final product with a low particle size suitable for metal ion batteries.
[0104] There may be some agglomerates of the porous carbon framework during the CVI process in the FBR. Therefore, the particle size of the intermediate particles may be higher than that of the porous carbon framework.
[0105] The pulverization can be performed by different types of pulverization devices such as mills such as wet mills, ball mills, air flow pulverization, high shear stirring, ultrasound, etc. Preferably, due to the reactivity of the intermediate particles, the pulverization is performed in a dry mill immediately after the infiltration is completed, because the electroactive materials deposited by the CVI process may be reactive. For example, silicon deposited by silane contains a large number of Si-H bonds. These bonds are reactive to organic molecules and water. Therefore, the presence of oxygen or organic solvents may lead to exothermic reactions, which lead to the destruction and / or degradation of the Si / C composite material to an amount lower than that required for commercial metal ion battery materials.
[0106] Among dry mills, jet mills are preferred due to their ability to grind to lower sizes. Jet mills utilize high-speed jets of compressed air or inert gas to cause particles to collide with each other. Jet mills can be used for feedstocks up to about 1 mm in size, and are known to easily achieve sizes on the order of 1 μm with less energy input.
[0107] There are different types of jet mills, such as rotary (periodic motion) and fluidized opposed jet. In the rotary type, the particles are accelerated by using the tangential gas force of the wall. Fluidized opposed jets work by a plurality of jets separated from each other at equal angles, and act on colliding particles whose collision trajectories are directed toward each other. When higher capacities are required, fluidized opposed jet mills are more suitable. The grinding action in both types of mills is achieved by the collision of particles with each other rather than with hard targets. This particular mode of action results in a pulverized product with a narrow particle size distribution, which is advantageous for incorporation into metal ion battery electrodes. Therefore, when an inert grinding gas with controlled composition (limited oxygen and water content) is used, the pulverized product has a high purity.
[0108] Rotary jet mills (e.g. spiral jet mills) or fluidized opposed jet mill designs can be used with diameters from 0.04 m up to several meters, with grinding gas pressures of 50 to 1000 kPa and a maximum starting particle size of 1 mm. The grinding gas is an inert gas such as nitrogen or argon, or a mixture thereof with low partial pressure air, water or oxygen.
[0109] The comminuted particles may optionally be classified according to size, for example by centrifugation or by sieving.
[0110] The intermediate particles can be passivated before the pulverizing step. That is, the particle surface can be treated to reduce its chemical reactivity, preferably minimizing or preventing any further oxidation of the particle surface in subsequent process steps or treatments. For example, the intermediate particles can be passivated in a low oxygen concentration environment, such as an environment where the oxygen concentration is less than 10% by volume oxygen. The intermediate particles can be passivated using an inert gas such as nitrogen. A low oxygen concentration gas mixture can also be used. Passivating the intermediate particles has the following advantages: undesirable further reactions of the intermediate particles are suppressed. For example, passivating the intermediate particles can remove reactive Si-H bonds. This helps to maintain the structure of the electroactive material deposited in the pores of the porous carbon skeleton derived from the CVI process, which is advantageous when the composite particles are used in metal ion batteries. The pulverizing step can also be carried out in a low oxygen concentration environment, such as in an inert gas or a low oxygen concentration gas mixture. Conveniently, the pulverizing step can be carried out in the same atmosphere as the optional passivation step.
[0111] The intermediate particles may be cooled prior to the comminution step, optionally in combination with a passivation step. The cooling may be to below 100°C, or below 50°C, or to ambient temperature. Cooling the intermediate particles has the advantage that the transfer of the intermediate particles to the comminution device is facilitated.
[0112] The method of the present invention can be a continuous process or an intermittent process. In a continuous process, it is necessary to carry out the passivation and cooling steps in a container separated from the FBR. The container separated from the FBR can be a pulverizing device.
[0113] Composite particle products
[0114] One benefit of the present invention is that the properties of the composite particle product can be controlled by selecting the properties of the porous carbon skeleton raw material. This is achieved for the following reasons: the inventors have found that due to the relative μm-length scale of the fracture compared to the nm-length scale of the functional units of the composite particles, the pulverization can be carried out without a significant level of damage. In other words, the pulverization step provides the desired particle size of the composite particle product while maintaining the ideal nanostructure obtained by depositing the electroactive material into a porous carbon skeleton including micropores and / or mesopores using CVI. For example, both the intermediate particles and the composite particles can include a plurality of nano-sized domains of electroactive materials in elemental form located in the micropores and / or mesopores of the porous carbon skeleton. As used herein, the term "nano-sized domain" refers to a nano-sized electroactive material body located in the pores of the porous carbon skeleton. The maximum size of the nano-sized silicon domain is limited by the pore size of the pore in which the silicon is located.
[0115] In general, composite particles are particulate materials in which nano-sized domains of electroactive materials occupy the pore volume of a porous carbon framework, wherein the pore volume includes micropores and / or mesopores. It has been found that this particle configuration provides electroactive materials having very high gravimetric and volumetric capacities after lithiation, as well as high reversible capacity retention over multiple charge-discharge cycles.
[0116] Without being bound by theory, it is believed that locating the nano-sized electroactive domains within the micropores and / or mesopores first provides a fine electroactive structure that can be lithiated and delithiated without excessive structural stress. It is believed that these very fine electroactive domains have a lower resistance to elastic deformation and a higher fracture resistance than larger electroactive structures. By ensuring that a higher proportion of the pore volume is occupied by the electroactive material, the composite particles can have a high capacity. In addition, by locating the nano-sized electroactive domains within the micropores and / or mesopores, only a small area of the electroactive surface is accessible to the electrolyte, thereby limiting SEI formation.
[0117] In some cases, composite particles prepared by the present invention may include pores in which fully encapsulated void spaces are capped by electroactive materials, thereby preventing electrolyte from entering the void spaces.
[0118] The particle size of the composite particles can be targeted by controlling the comminution step and the optional step of classifying the particles according to size to provide the desired particle size distribution for the end use application.
[0119] Due to the comminution of the intermediate particles in step (c), the D 50 The particle size is smaller than that of the porous carbon skeleton. 50 Therefore, the D of the composite particles obtained in step (c) 50 The particle size can be, for example, up to 50 μm, as long as the D 50 The particle size is still large. For example, the D 50 The particle size may be no greater than 40 μm, or no greater than 30 μm, or no greater than 25 μm.
[0120] It is preferred that the D of the composite particles 50 The particle size may not exceed 20 μm. For example, the D 50 The particle size may be no more than 15 μm, or no more than 12 μm, or no more than 10 μm, or no more than 9 μm, or no more than 8 μm, or no more than 7 μm, or no more than 6.5 μm, or no more than 6 μm, or no more than 5.5 μm, or no more than 5 μm, or no more than 4.5 μm, or no more than 4 μm, or no more than 3.5 μm.
[0121] D of composite particles 50The particle size may be at least 1 μm, or at least 2 μm, or at least 3 μm, or at least 4 μm, or at least 5 μm.
[0122] Preferably, the D of the composite particles 50 The particle size is in the range of 0.5 to 20 μm, or in the range of 0.5 to 15 μm, or in the range of 0.5 to 12 μm, or in the range of 0.5 to 10 μm, or in the range of 0.5 to 8 μm, or in the range of 0.5 to 9 μm, or in the range of 0.5 to 7 μm. Composite particles within these size ranges and having the porosity and pore size distribution described herein are ideally suited for use in anodes of metal ion batteries due to their dispersibility in slurries, their structural robustness, their capacity retention with repeated charge-discharge cycles, and their suitability for forming a dense electrode layer having a uniform thickness in the conventional range of 20 to 50 μm.
[0123] D of composite particles 10 The particle size may be at least 0.2 μm, or at least 0.5 μm, or at least 0.8 μm, or at least 1 μm, or at least 1.5 μm, or at least 2 μm.
[0124] D of composite particles 90 The particle size may be no greater than 40 μm, or no greater than 30 μm, or no greater than 20 μm, or no greater than 15 μm, or no greater than 10 μm, or no greater than 8 μm, or no greater than 6 μm.
[0125] Preferably, the D of the porous carbon skeleton in step (a) is 50 The particle size is at least 30 μm, and the D of the composite particles obtained in step (c) is 50 The particle size does not exceed 20 μm. More preferably, the D of the porous carbon skeleton in step (a) 50 The particle size is at least 40 μm, and the D 50 The particle size does not exceed 20 μm. More preferably, the D of the porous carbon skeleton in step (a) 50 The particle size is at least 50 μm, and the D of the composite particles obtained in step (c) is 50 The particle size does not exceed 20μm.
[0126] Preferably, the BET surface area of the composite material of the present invention does not exceed 300 m 2 / g, or not more than 250m 2 / g, or not more than 200m 2 / g, or not more than 150m 2 / g, or not more than 100m 2 / g, or not more than 80m 2 / g, or not more than 60m 2 / μ, or not more than 40m 2 / g, or not more than 30m 2 / g, or not more than 25m 2 / g, or not more than 20m 2 / g, or not more than 15m 2 / g, or not more than 10m 2 / g. Generally, a low BET surface area is preferred to minimize the formation of a solid electrolyte interface (SEI) layer at the surface of the composite particles during the first charge-discharge cycle of an anode comprising the particulate material of the present invention. However, too low a BET surface area results in unacceptably low charge rates and capacities due to the inaccessibility of the bulk of the electroactive material to the metal ions in the surrounding electrolyte. For example, the BET surface area is preferably at least 0.1 m 2 / g, or at least 1m 2 / g, or at least 2m 2 / g, or at least 5m 2 / g. For example, the BET surface area can be 2 / g to 25m 2 / g, more preferably in the range of 2 to 15 m 2 / g range.
[0127] Preferably, at least 90 weight percent, more preferably at least 95 weight percent, more preferably at least 98 weight percent, and more preferably at least 99 weight percent of the electroactive mass in the composite particles is located within the internal pore volume of the porous carbon framework, so that no or very little electroactive material is located on the outer surface of the composite particles.
[0128] Preferably, the volume of micropores and mesopores in the composite particles (ie in the presence of electroactive material) measured by nitrogen adsorption does not exceed 0.15×P1, or does not exceed 0.10×P1, or does not exceed 0.05×P1, or does not exceed 0.02×P1.
[0129] The weight ratio of the electroactive material such as silicon to the porous carbon skeleton in the composite particles can be determined by elemental analysis. The weight percentage of the electroactive material and the carbon in the composite particles is determined using elemental analysis. Optionally, the amount of hydrogen, nitrogen and oxygen can also be determined by elemental analysis. Preferably, the weight percentage of carbon (and optional hydrogen, nitrogen and oxygen) in the individual porous carbon skeleton is also determined using elemental analysis. Determining the weight percentage of carbon in the porous carbon skeleton itself takes into account the possibility that the porous carbon skeleton contains a small amount of heteroatoms in its molecular skeleton. The two measurements performed together make it possible to reliably determine the weight percentage of silicon relative to the entire porous carbon skeleton.
[0130] The electroactive material (e.g. silicon) content is preferably determined by ICP-OES (Inductively Coupled Plasma-Optical Emission Spectroscopy). A variety of ICP-OES instruments are commercially available, such as The carbon content (and, if desired, the hydrogen content, nitrogen content, and oxygen content) of the composite particles and the porous carbon framework itself is preferably determined by IR absorption. A suitable instrument for determining the carbon content, hydrogen content, nitrogen content, and oxygen content is Micro Elemental Analyzer (available from Leco Corporation).
[0131] Suitably, when the electroactive material is silicon, the composite particles comprise from 30wt% to 80wt% silicon, preferably from 45wt% to 65wt% silicon.
[0132] The composite particles preferably have a low total oxygen content. Oxygen may be present in the composite particles, for example, as part of the porous carbon framework or as an oxide layer on any exposed silicon surface. Preferably, the total oxygen content of the composite particles is less than 15 wt%, more preferably less than 10 wt%, more preferably less than 5 wt%, for example less than 2 wt%, or less than 1 wt%, or less than 0.5 wt%.
[0133] When the electroactive material is silicon, the weight ratio of silicon to the porous carbon framework in the composite particles is preferably in the range of [0.5×P1 to 2.2×P1]: 1. This relationship takes into account the density of silicon and the pore volume of the porous carbon framework to define the weight ratio of silicon, at which the pore volume occupied by silicon is about 20% to 95% by volume.
[0134] The composite particles generally have a charge capacity of 1200 to 2340 mAh / g upon initial lithiation. Preferably, the composite particles have a charge capacity of at least 1400 mAh / g upon initial lithiation.
[0135] As discussed above, certain types of composite particle products are targeted by using certain types of porous carbon frameworks. It will be understood that the pore structure of the porous carbon framework, such as micropores and / or mesopores, will be retained in the composite particle product. Certain types of composite particle products are discussed below. It will be understood that the characteristics of the types of composite particles discussed below should be considered in combination with the characteristics of the composite particles discussed above, such as particle size.
[0136] Composite particles 1
[0137] The composite particles 1 prepared by the method of the present invention include:
[0138] (a) a porous carbon framework comprising micropores and / or mesopores,
[0139] The total pore volume of the micropores and / or mesopores measured by gas adsorption is P1cm 3 / g, where P1 represents a natural number having a value of at least 0.7, and
[0140] Among them, PD measured by gas adsorption 50 Pore diameter does not exceed 5nm; and
[0141] (b) a plurality of elemental nano-sized silicon domains located within the micropores and / or mesopores of the porous carbon framework;
[0142] The weight ratio of silicon in the composite particles to the porous carbon framework is in the range of [0.5 x P1 to 1.3 x P1]: 1. This corresponds to about 20 to 55% silicon volume of the total micropore / mesopore volume (in the uncharged state).
[0143] The composite particle 1 may be prepared using the porous carbon skeleton 1 as a raw material. Therefore, the pore structure of the porous carbon skeleton 1 may exist in the composite particle 1.
[0144] Preferably, the weight ratio of silicon to carbon is in the range of [0.55×P1 to 1.1×P1]:1, or in the range of [0.6×P1 to 1.1×P1]:1, or in the range of [0.6×P1 to 1×P1]:1, or in the range of [0.6×P1 to 0.95×P1]:1, or in the range of [0.6×P1 to 0.9×P1]:1, or in the range of [0.65×P1 to 0.9×P1]:1, or in the range of [0.65×P1 to 0.85×P1]:1, or in the range of [0.65×P1 to 0.8×P1]:1, or in the range of [0.7×P1 to 0.8×P1]:1.
[0145] Preferably, silicon occupies about 25% to about 45%, more preferably about 25% to 40% of the internal pore volume of the porous carbon framework. Within these preferred ranges, the pore volume of the porous carbon framework effectively accommodates the expansion of silicon during charge and discharge, but avoids excessive pore volume, which is detrimental to the volumetric capacity of the particle material. However, the amount of silicon is not so high as to prevent effective lithiation due to insufficient metal ion diffusion rate or insufficient expansion volume resulting in mechanical resistance to lithiation.
[0146] D of composite particle 1 50 The particle size may be in the range of 0.5 to 50 μm. Optionally, D 50 The particle size may not exceed 20 μm.
[0147] For example, the D of composite particle 1 50The particle size may be in the range of 1 to 25 μm, or in the range of 1 to 20 μm, or in the range of 2 to 20 μm, or in the range of 2 to 15 μm, or in the range of 3 to 15 μm.
[0148] Composite Particle 2
[0149] The composite particles 2 prepared by the method of the present invention include:
[0150] (a) A porous carbon framework comprising micropores and mesopores, wherein
[0151] (i) wherein the total pore volume of the micropores and mesopores measured by gas adsorption is P1cm 3 / g, where the value of P1 is at least 0.6,
[0152] (ii) The volume fraction of micropores based on the total volume of micropores and mesopores In the range of 0.1 to 0.9;
[0153] (iii) Volume fraction of pores with a pore size of 20 nm or less based on the total volume of micropores and mesopores is at least 0.75, and
[0154] (iv) D of the porous carbon skeleton 50 Particle size less than 20 μm;
[0155] (b) a plurality of nano-sized elemental silicon domains located within the micropores and / or mesopores of the porous carbon framework;
[0156] The weight ratio of silicon in the composite particles to the porous carbon skeleton is in the range of [1×P1 to 2.2×P1]:1.
[0157] The composite particle 2 may be prepared using the porous carbon skeleton 2 as a raw material. Therefore, the pore structure of the porous carbon skeleton 2 may exist in the composite particle 2.
[0158] Composite particles 2 are particularly suitable for use in "hybrid" electrodes comprising a combination of graphite and composite particles.
[0159] The weight ratio of silicon to the porous carbon skeleton in the composite particles is in the range of [1×P1 to 2.2×P1]: 1. Considering that the density of silicon is about 2.3 g / cm 3 , a weight ratio of [1×P1]:1 corresponds to an occupation of the pores of the porous carbon framework by silicon of about 43% v / v. An upper limit of the ratio of [2.2×P1]:1 corresponds to an occupation of the pores of the porous carbon framework by silicon of about 95% v / v.
[0160] Preferably, the weight ratio of silicon to the porous carbon skeleton is at least 1.1×P1, more preferably at least 1.15×P1, more preferably at least 1.2×P1, more preferably at least 1.25×P1, more preferably at least 1.3×P1, more preferably at least 1.35×P1, more preferably at least 1.4×P1.
[0161] In the case where the porous carbon framework comprises a relatively high ratio of mesopores to micropores (e.g. In the range of 0.2 to 0.5 or in the range of 0.3 to 0.5), the weight ratio of silicon to carbon can also be higher, for example at least 1.45×P1, more preferably at least 1.5×P1, more preferably at least 1.55×P1, more preferably at least 1.6×P1, more preferably at least 1.65×P1, more preferably at least 1.5×P1.
[0162] In another preferred embodiment, the minimum weight ratio of silicon to the porous carbon framework is at least The value given by The value given by The value given by The value given by Therefore, in the mesoporous fraction With higher values, the amount of silicon in the composite particle 2 is also higher. This relationship between the mesopore fraction and the minimum weight ratio of silicon to the porous carbon framework ensures that the porous carbon framework with a higher mesopore fraction is occupied to a greater extent by silicon, thereby optimizing the volumetric capacity of the composite particle 2. Ensuring that the porous carbon framework with a higher mesopore fraction has a higher minimum silicon loading also reduces the likelihood that larger micropores will be partially occupied by silicon, thereby reducing the silicon surface area exposed to the electrolyte, thereby limiting undesirable SEI formation.
[0163] In other embodiments, the maximum weight ratio of silicon to porous carbon framework is no more than The value given by The relationship between the mesopore fraction and the maximum weight ratio of the porous carbon framework ensures that the porous carbon framework with a higher micropore fraction is not overfilled with silicon.
[0164] The D50 particle size of the composite particles 2 may be in the range of 0.5 to 20 μm. 50 The particle size is not more than 12 μm, or not more than 10 μm, or not more than 8 μm.
[0165] For example, the D of composite particle 2 50 The particle size may be in the range of 1 to 12 μm, or 1 to 10 μm, or 2 to 10 μm, or 3 to 8 μm.
[0166] D of composite particle 2 10 The particle size is preferably at least 0.5 μm.
[0167] D of composite particle 2 90 The particle size is preferably not more than 12 μm, or not more than 10 μm.
[0168] Composite particles 3
[0169] The composite particles 3 prepared by the method of the present invention include:
[0170] (a) a porous carbon framework comprising micropores and / or mesopores,
[0171] The total pore volume of micropores and mesopores measured by gas adsorption is at least 0.7 cm 3 / g,
[0172] The PD measured by gas adsorption 50 Pore diameter does not exceed 2nm; and
[0173] (b) an electroactive material located in the micropores and / or mesopores of the porous carbon framework;
[0174] wherein the composite particle D 90 The particle size does not exceed 10μm.
[0175] The composite particle 3 may be prepared using the porous carbon skeleton 3 as a raw material. Therefore, the pore structure of the porous carbon skeleton 3 may exist in the composite particle 3.
[0176] Composite particle 3 relates to a particulate material in which the porous carbon framework has a high total volume of micropores and mesopores, wherein pores with a diameter of no more than 2 nm account for at least 50% of the total pore volume. This pore structure can be derived from the porous carbon framework 3. Composite particle 3 has a particle size distribution that is heavily biased towards particles with a diameter of no more than 10 μm. It has been found that the combination of small particle size and highly differentiated pore volume provides an electroactive material with high resistance to mechanical degradation during electrode manufacturing.
[0177] D of composite particle 3 90 The particle size is preferably no more than 9.5 μm, or no more than 9 μm, or no more than 8.5 μm, or no more than 8 μm, or no more than 7.5 μm, or no more than 7 μm, or no more than 6.5 μm, or no more than 6 μm, or no more than 5.5 μm, or no more than 5 μm, or no more than 4.5 μm, or no more than 4 μm.
[0178] D of composite particle 3 50 The particle size is preferably in the range of 0.5 to 7 μm. Optionally, D 50The particle size may be at least 1 μm, or at least 1.5 μm, or at least 2 μm, or at least 2.5 μm, or at least 3 μm.
[0179] Optionally, D 50 The particle size may be no greater than 6.5 μm, or no greater than 6 μm, or no greater than 5.5 μm, or no greater than 5 μm, or no greater than 4.5 μm, or no greater than 4 μm, or no greater than 3.5 μm.
[0180] For example, the D of composite particle 3 50 The particle size may be in the range of 1 to 6.5 μm, or in the range of 1.5 to 6 μm, or in the range of 2 to 5.5 μm, or in the range of 2.5 to 5 μm, or in the range of 3 to 4.5 μm.
[0181] D of composite particle 3 10 The particle size is preferably at least 0.5 μm.
[0182] D of composite particle 3 99 The particle size is preferably not more than 25 μm.
[0183] The amount of electroactive material in the composite particles 3 is preferably selected so that no more than about 55% of the internal pore volume of the porous carbon framework is occupied by the electroactive material (in an uncharged state). Preferably, the electroactive material occupies about 25% to about 45% of the internal pore volume of the porous carbon framework, more preferably about 25% to 40% of the internal pore volume of the porous carbon framework.
[0184] In the case where the electroactive material is silicon, the weight ratio of silicon to the porous carbon framework is preferably [0.5×P1 to 1.3×P1]: 1. More preferably, the weight ratio of silicon to carbon is in the range of [0.55×P1 to 1.1×P1]: 1, or in the range of [0.6×P1 to 1.1×P1]: 1, or in the range of [0.6×P1 to 1×P1]: 1, or in the range of [0.6×P1 to 0.95×P1]: 1, or in the range of [0.6×P1 to 0.9×P1]: 1, or in the range of [0.65×P1 to 0.9×P1]: 1, or in the range of [0.65×P1 to 0.85×P1]: 1, or in the range of [0.65×P1 to 0.8×P1]: 1, or in the range of [0.7×P1 to 0.8×P1]: 1.
[0185] Carbon coating
[0186] The method of the present invention may optionally include an additional step including depositing a conductive coating / preferably a carbon-based coating on the composite particles. Suitably, the conductive carbon-based coating can be obtained by chemical vapor deposition (CVD). CVD is a method well known in the art and includes thermally decomposing a volatile carbon-containing gas (e.g., ethylene) onto the surface of a particulate material. Alternatively, a carbon-based coating can be formed by depositing a solution of a carbon-containing compound onto the surface of the particulate material and then thermally decomposing it. The conductive coating (e.g., a carbon-based coating) has sufficient permeability to allow lithium to approach the interior of the composite particles without excessive resistance, thereby not reducing the rate performance of the composite particles. For example, the thickness of the conductive coating can be suitably in the range of 2 to 30 nm. Optionally, the conductive coating can be porous, and / or can only partially cover the surface of the composite particles.
[0187] The conductive coating has the following advantages: it further reduces the BET surface area of the composite particles by smoothing any surface defects and by filling any remaining surface micropores, thereby further reducing the first cycle loss. In addition, the conductive coating improves the electronic conductivity of the surface of the composite particles, thereby reducing the need for conductive additives in the electrode composition, and also creates an optimal surface for forming a stable SEI layer, resulting in improved capacity retention during cycling.
[0188] Preferably, the BET surface area of the composite particles after deposition of the conductive coating is less than 50, less than 30, less than 20, more preferably less than 10, or less than 5 m 2 / g.
[0189] Final use of the product
[0190] The method of the present invention may optionally include the further step of forming an electrode composition comprising the composite particles (optionally wherein the composite particles have been coated with a conductive carbon coating). The electrode composition may include at least one further component selected from the group consisting of: (i) a binder; (ii) a conductive additive; and (iii) a further particulate electroactive material.
[0191] The method of the present invention may optionally comprise the further step of forming a slurry comprising the composite particles (optionally wherein the composite particles have been coated with a conductive carbon coating) and a solvent.
[0192] Products defined by method
[0193] The present invention also provides a particulate material comprising composite particles that can be obtained by the method of the present invention. The nanostructure of the electroactive material deposited by the CVI process of the present invention is different from the nanostructure of the electroactive material deposited by other means. In addition, because the composite particles are obtained from the CVI process and the subsequent comminution process, they can be distinguished from particles of similar size prepared without the subsequent comminution step. For example, the comminution step produces a fractured surface that can be observed by microscopy. Therefore, the composite particles that can be obtained by the method of the present invention can be distinguished from the composite particles obtained by other means. Example
[0194] The silicon-carbon composite was synthesized in a vertical bubbling fluidized bed reactor comprising a stainless steel cylindrical vessel with an inner diameter of 83 mm. 126 g of the feed material having a BET surface area of 1777 m 2 / g, total pore volume is 0.78cm 3 / g、PD 10 =0.97nm, PD 50 =1.15nm, PD 90 =2.23nm and A premixed mixture of porous carbon particles is prepared. A low flow rate of inert gas (nitrogen) is injected into the reactor to remove any oxygen. The reactor is then heated to a reaction temperature of 420 to 440°C, and 1.25% v / v of monosilane gas diluted in nitrogen is supplied to the bottom of the reactor at a flow rate sufficient to fluidize the carbon skeleton particles for a period of 32.3 hours (Sample 1) or 37 hours (Sample 2). Once the reaction time is completed, the reactor atmosphere is switched to pure nitrogen while maintaining fluidization, and this purge lasts for 30 minutes. Thereafter, the furnace is cooled to ambient temperature over a period of several hours. When ambient temperature is reached, the furnace atmosphere is gradually switched to air over a period of several hours.
[0195] Add the product to MC The 30% slurry was added to the feed tray of a 30 mill and ground in an inert atmosphere. The ring pressure was set to 650 kPa and the Venturi pressure was set to 700 kPa. The product was micronized and then collected in a suitable container. The material properties of the two composite materials are given in Table 1.
[0196] Table 1
[0197]
[0198] Preparation of negative electrode
[0199] The negative electrode coating (anode) was prepared from each material of Samples 1 and 2. (Conductive carbon) dispersion in CMC binder in Thinky TM The Si-C composite material was added to the mixture and mixed in a Thinky TM The mixture was mixed in a mixer for 30 minutes. Then, an SBR binder was added to provide a CMC:SBR ratio of 1:1 to obtain a slurry in which the weight ratio of Si-C composite material:CMC / SBR:carbon black was 70%:16%:14%. The slurry was placed in a Thinky TM The mixture was mixed in a mixer for another 30 minutes, and then coated onto a 10 μm thick copper substrate (current collector) and dried at 50° C. for 10 minutes, and then dried at 110° C. for 12 hours, thereby forming a negative electrode.
[0200] Battery manufacturing and recycling
[0201] Full battery manufacturing
[0202] A full button cell was prepared using a 0.8 cm radius circular negative electrode cut from a coating made using samples 1 and 2 (as described above), a porous polyethylene separator, and a nickel manganese cobalt (NMC532) positive electrode. The positive and negative electrodes were designed to form a balanced pair so that the capacity ratio of the positive electrode to the negative electrode was 0.9. An electrolyte of 1 M LiPF6 in a 7:3 solution of EMC / FEC (ethyl methyl carbonate / fluoroethylene carbonate) containing 3 wt % ethylene carbonate was then added to the cell before sealing.
[0203] The button cell was cycled as follows: a constant current was applied at a rate of C / 25 to lithiate the anode with a cutoff voltage of 4.3V. When the cutoff was reached, a constant voltage of 4.3V was applied until a cutoff current of C / 100 was reached. The cell was then left to rest in the lithiated state for 10 minutes. The anode was then delithiated at a constant current of C / 25 with a cutoff voltage of 2.75V. The cell was then left to rest for 10 minutes. After this initial cycle, a constant current of C / 2 was applied to lithiate the anode with a cutoff voltage of 4.3V, followed by a constant voltage of 4.3V with a cutoff current of C / 40 and a rest time of 5 minutes. The anode was then delithiated at a constant current of C / 2 with a cutoff of 2.75V. This process was then repeated for the desired number of cycles.
[0204] The charge (lithiation) and discharge (delithiation) capacities of the silicon-carbon composite material per unit mass for each cycle were calculated, and the capacity retention value of each discharge capacity was calculated as a percentage of the discharge capacity of the second cycle. The first cycle loss (FCL) is (1-(1st delithiation capacity / 1st lithiation capacity))×100%. The key values are the average of 3 button cells for each material and are listed in Table 2.
[0205] Table 2
[0206]
Claims
1. A method for preparing composite particles, the method comprising: (a) providing a particulate porous carbon framework comprising micropores and / or mesopores, wherein the porous carbon framework (i) D 50 The particle size is at least 20 μm; (ii) The particle size distribution span is less than 3, where the particle size distribution span is defined as (D 90 -D 10 ) / D 50 ; (iii) The total volume of micropores and mesopores is P1 cm 3 / g, wherein the value of P1 is in the range of 0.5 to 2.5; and (iv) PD 50 The pore size is no more than 2 nm, where PD 50 It refers to the 50th percentile volume-based pore size based on the total volume of micropores and mesopores; According to ISO 15901-2 and ISO 15901-3, nitrogen adsorption was used at 77 K down to 10 -6 The relative pressure p / p0 is determined by using quenched solid density functional theory (QSDFT) to determine the total volume of the micropores and mesopores and the pore size distribution; (b) depositing an electroactive material selected from silicon, tin, aluminum, germanium and alloys thereof into the micropores and / or mesopores of the porous carbon framework using chemical vapor infiltration in a fluidized bed reactor to provide intermediate particles; and (c) pulverizing the intermediate particles to provide the composite particles.
2. The method of claim 1, further comprising transferring the intermediate particles to a comminution device before step (c). The method of claim 1 , wherein the electroactive material is silicon.
4. The method of claim 1, wherein the intermediate particles and the composite particles comprise a plurality of nano-sized domains of the electroactive material in elemental form located within the micropores and / or mesopores of the porous carbon framework.
5. The method of claim 1, wherein the chemical vapor infiltration is performed at a temperature ranging from 200 to 1,250°C, or from 400 to 700°C, or from 450 to 550°C, or from 450 to 500°C.
6. The method according to claim 1, further comprising the step of cooling the intermediate particles before comminuting the intermediate particles.
7. The method of claim 6, wherein the cooling is to a temperature below 100°C or below 50°C, or to ambient temperature.
8. The method according to claim 1, further comprising the step of passivating the intermediate particles before pulverizing the intermediate particles.
9. The method according to claim 8, wherein the passivation is performed in an inert gas or in an environment with an oxygen concentration of less than 10% by volume of oxygen.
10. The method according to claim 2, wherein the comminution device is a jet mill.
11. The method according to claim 1, wherein the step of pulverizing the intermediate particles is performed in an inert gas or in an environment having an oxygen concentration of less than 10% by volume of oxygen.
12. The method of claim 1, wherein the method is a continuous process, or wherein the method is a batch process.
13. The method according to claim 1, wherein the total pore volume of micropores and / or mesopores of the porous carbon skeleton measured by gas adsorption is P1 cm 3 / g, wherein the value of P1 is at least 0.6, or at least 0.7, or at least 0.75, or at least 0.8, or at least 0.85, or at least 0.9, or at least 0.95, or at least 1, or at least 1.05, or at least 1.1, or at least 1.
2.
14. The method according to claim 1, wherein the total pore volume of micropores and / or mesopores of the porous carbon skeleton measured by gas adsorption is P1 cm 3 / g, wherein the value of P1 is not more than 2.2, or not more than 2, or not more than 1.8, or not more than 1.6, or not more than 1.5, or not more than 1.4, or not more than 1.
3.
15. The method according to claim 14, wherein the total pore volume of micropores and / or mesopores of the porous carbon skeleton measured by gas adsorption is P1 cm 3 / g, wherein the value of P1 is in the range of 0.6 to 2.5, or in the range of 0.7 to 2, or in the range of 0.7 to 1.
2.
16. The method according to claim 1, wherein the D of the porous carbon framework is 50 The particle size ranges from 60 to 150 μm.
17. The method according to claim 1, wherein the D of the porous carbon framework 50 The particle size is at least 30 μm, or at least 40 μm, or at least 50 μm, or at least 60 μm, or at least 70 μm, or at least 80 μm.
18. The method according to claim 1, wherein the D of the porous carbon framework is 50 The particle size is no more than 1000 μm, or no more than 500 μm, or no more than 250 μm, or no more than 150 μm.
19. The method according to claim 1, wherein the D of the porous carbon framework is 10 The particle size is at least 5 μm, or at least 15 μm, or at least 40 μm, or at least 50 μm, or at least 60 μm, or at least 70 μm.
20. The method according to claim 1, wherein the D of the porous carbon framework is 90 The particle size is not more than 1,500 μm, or not more than 1000 μm, or not more than 750 μm, or not more than 500 μm, or not more than 200 μm.
21. The method according to claim 1, wherein the D of the porous carbon framework 98 The particle size is not more than 1,550 μm, or not more than 1,050 μm, or not more than 800 μm, or not more than 550 μm, or not more than 250 μm.
22. The method of claim 1, wherein the porous carbon framework has a BET surface area of at least 750 m 2 / g, or at least 1,000 m 2 / g, or at least 1,250 m 2 / g, or at least 1,500 m 2 / g.
23. The method of claim 1, wherein the porous carbon framework has a BET surface area of no more than 4,000 m 2 / g, or not more than 3,500 m 2 / g, or not more than 3,250 m 2 / g, or not more than 3,000 m 2 / g.
24. The method of claim 23, wherein the porous carbon framework has a BET surface area of 1,500 to 3,000 m 2 / g.
25. The method according to claim 1, wherein the porous carbon framework is measured by PD 50 The pore diameter is no more than 1.5 nm, or no more than 1 nm.
26. The method according to claim 1, wherein the D of the composite particles 50 The particle size ranges from 0.5 to 20 µm.
27. The method according to claim 26, wherein the D of the composite particles 50 The particle size is at least 1 µm, or at least 2 µm, or at least 3 µm, or at least 4 µm, or at least 5 µm.
28. The method according to claim 26, wherein the D of the composite particles 50 The particle size is not more than 20 μm, or not more than 15 µm, or not more than 12 µm, or not more than 10 µm, or not more than 9 µm, or not more than 8 µm, or not more than 7 µm, or not more than 6.5 µm, or not more than 6 µm, or not more than 5.5 µm, or not more than 5 µm, or not more than 4.5 µm, or not more than 4 µm, or not more than 3.5 µm.
29. The method according to claim 1, wherein the D of the composite particles 10 The particle size is at least 0.2 µm, or at least 0.5 µm, or at least 0.8 µm, or at least 1 µm, or at least 1.5 µm, or at least 2 µm.
30. The method of claim 1, wherein the D of the composite particles 90 The particle size is not more than 80 µm, or not more than 60 µm, or not more than 40 µm, or not more than 30 µm, or not more than 25 µm, or not more than 20 µm, or not more than 10 μm.
31. The method of claim 1, wherein the composite particles have a particle size distribution span of no more than 5, or no more than 4, or no more than 3, or no more than 2, or no more than 1.
5.
32. The method of claim 1, wherein the electroactive material is silicon, wherein the pore volume of the composite particles is expressed as P1 cm 3 / g, and wherein for the composite particles, the weight ratio of silicon in the composite particles to the porous carbon skeleton is in the range of [0.5×P1 to 2.2×P1]:1, or in the range of [1×P1 to 2.2×P1]:1, or in the range of [0.5×P1 to 1.3×P1]:
1.
33. The method of claim 1, wherein the electroactive material is silicon, and wherein the composite particles comprise 30 wt% to 80 wt% silicon, or 45 wt% to 65 wt% silicon.
34. The method of claim 1, wherein the composite particles comprise no more than 15 wt% oxygen, or no more than 10 wt% oxygen.
Citation Information
Patent Citations
Lithium secondary battery
JP2003100284A
Novel materials with extremely durable intercalation of lithium and manufacturing methods thereof
WO2017040299A1
Decomposition of silicon-containing precursors on porous scaffold materials
WO2018165610A1